Analisis Pengaruh Keandalan, Responsivitas, Jaminan, Empati, Dan Bukti Fisik Terhadap Kepuasan Pelanggan Dalam Layanan Cash On Delivery (COD) J&T Express Di Kecamatan Tanggul Kabupaten Jember - Nanis Faizatus Zakiyah; Ahmad Sauqi; Tamriatin Hidayah (GLOBAL SCIENTS PUBLISHER, 2026)
Abstract The rapid growth of e-commerce has increased public demand for fast, secure, and reliable delivery services. One of the most widely used payment methods in online transactions is Cash On Delivery (COD). However, several service issues may affect customer satisfaction. This study aims to analyze the influence of reliability, responsiveness, assurance, empathy, and tangibles on customer satisfaction in J&T Express Cash On Delivery services in Tanggul District, Jember Regency. This study employed a quantitative approach using questionnaires distributed to customers who had used J&T Express COD services. The sampling technique used purposive sampling with 60 respondents. Data were analyzed using multiple linear regression supported by validity, reliability, classical assumption, t-test, and F-test analyses. The results indicate that reliability, responsiveness, assurance, and tangibles have a positive and significant effect on customer satisfaction, while empathy has no significant effect. Simultaneously, all service quality dimensions significantly influence customer satisfaction. These findings suggest that improving service quality is essential for enhancing customer satisfaction J&T Express COD services.